Surgical Management and Recent Advances in Inguinal Hernia - Guo, Runjie; Wu, Shile (Journal of Contemporary Medical Practice, 2025)
Inguinal hernia is the most common type of external abdominal hernia encountered in clinical practice, with a significantly higher incidence in males than in females. Surgical repair remains the only effective treatment option. This article provides a comprehensive review of the etiology, risk factors, surgical indications, and classification of inguinal hernias. It offers a detailed comparison between traditional open repair techniques (such as the Bassini, Shouldice, McVay, and Lichtenstein methods) and minimally invasive approaches, including TAPP (transabdominal preperitoneal), TEP (totally extraperitoneal), and robot-assisted surgeries, highlighting their technical features, suitable patient populations, and clinical outcomes. In addition, recent advances are discussed in several key areas: the development of mesh materials (including biodegradable, composite, and functionally modified meshes), innovations in anesthesia and analgesia (such as nerve blocks, long-acting sustained-release agents, and multimodal pain management), the expansion of ambulatory surgery models, and personalized treatment strategies. Future research is expected to focus on artificial intelligence–assisted decision-making and surgical navigation, balancing standardization with individualization of care, and building intelligent management platforms. These efforts aim to advance inguinal hernia treatment toward greater precision, minimally invasiveness, and intelligent integration.